PENGARUH PENGEKANGAN GFRP TERHADAP KEKUATAN DAN DAKTILITAS KOLOM BETON BERTULANG PERSEGI AKIBAT BEBAN SIKLIK - Karmila Achmad; Agoes SMD; Tavio . (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2012)
Karmila Achmad1, Agoes SMD2 & Tavio31Mahasiswa Program Magister Teknik Sipil Struktur Universitas Brawijaya, Malang dan Dosen Politeknik NegeriBalikpapan2 Guru Besar Teknik Sipil Struktur Universitas Brawijaya, Malang3Dosen Teknik Sipil Struktur-FTSP Institut Teknologi Sepuluh Nopember, SurabayaEmail : milabpp@yahoo.co.idABSTRACTThe aim of this research is to get improving of strength and ductility in column specimen giventhe GFRP strengthener (Glass Fiber Reinforced Polymer) toward with original column, by using thecyclic load as the fix representative of quake load. There are two specimens full scale used. Theyare C-1 (original column) and C-1G (column with GFRP strengthener 1 layer). From the researchgot Pmax sequentially is 278,9 kN and 372.4 kN, and dmax is 53.24 mm and 56.78 mm, each for C-1and C-1G. For C-1 column, the concrete gets damage in plastic hinge zone at drift ratio 3.5%indicated by bending of longitudinal steel bar and spalling of cover concrete. The test for C-1G endsin third cycle at drift ratio 5% and gets damage in fracture of GFRP in plastic hinge zone. Thedamage is the changing of resin color the circumferential direction in three spots. They are as longas 10, 11 and 18 cm. Ductility index taken on three positions are plastic hinge zone, column with ahalf high effective and as high as effective column. From the analyze result got ductility index C-1on the three positions are 1.65; 1.70; 1,97 and ductility index C-1G are 1,44; 1,44 and 1,38 each forplastic hinge zone, a half high effective and as high as effective columnKey words : ductility, GFRP, strength, external confinement, cyclic